2011
DOI: 10.1038/jcbfm.2011.74
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Human and Rat Cerebral Arteries Constrict to Increases in Flow: Role of 20-HETE and TP Receptors

Abstract: Elevation of intraluminal pressure increases vasomotor tone, which thought to have a substantial role in regulation of cerebral blood flow (CBF). Interestingly, responses of cerebral vessels to increases in flow varied and have not been studied in human cerebral arteries. We hypothesized that increases in flow elicit constrictions of isolated human and rat cerebral arteries and aimed to elucidate the underlying mechanisms. Human cerebral arteries and rat middle cerebral arteries constricted to increases in flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 58 publications
5
72
1
1
Order By: Relevance
“…Vascular overproduction of 20-HETE decreases endothelial-dependent vasodilation, and increases oxidative stress, vasoconstriction and blood pressure (Wang et al, 2006). Furthermore, vasoconstriction by 20-HETE is mediated by activation of TP receptor in many vascular beds Muller et al, 2007;Schwartzman et al, 1989;Toth et al, 2011), including the mouse aorta as shown by our results. We also found that TCDD increases the contribution of the TP receptor to AA-mediated vasoconstriction, further implicating the potential contribution of 20-HETE to TCDDinduced vascular dysfunction.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Vascular overproduction of 20-HETE decreases endothelial-dependent vasodilation, and increases oxidative stress, vasoconstriction and blood pressure (Wang et al, 2006). Furthermore, vasoconstriction by 20-HETE is mediated by activation of TP receptor in many vascular beds Muller et al, 2007;Schwartzman et al, 1989;Toth et al, 2011), including the mouse aorta as shown by our results. We also found that TCDD increases the contribution of the TP receptor to AA-mediated vasoconstriction, further implicating the potential contribution of 20-HETE to TCDDinduced vascular dysfunction.…”
Section: Discussionsupporting
confidence: 52%
“…As noted earlier 20-HETE is predominately generated by CYP4A12 in male mice and in some vascular beds vasoconstriction by 20-HETE is dependent on subsequent cyclooxygenase metabolism to a TP receptor agonist Muller et al, 2007;Schwartzman et al, 1989;Toth et al, 2011). Thus, the mRNA expression of Cyp4a12 in the liver and kidney, and prostaglandin-endoperoxide synthase 2 (aka cyclooxygenase 2) was analyzed in the lung, representing the tissues where they are predominately expressed.…”
Section: Tcdd Induced Cyclooxygenase 2 In Lung But Not Cyp4a12 In LIVmentioning
confidence: 99%
“…On day 28 postimplantation mice were decapitated, the brains were removed, and segments of the MCAs were isolated using microsurgery instruments for functional studies, as reported (59,64). Segments of MCAs were mounted onto two glass micropipettes in an organ chamber in oxygenated (21% O 2-5% CO2-75% N2) Krebs= buffer (pH ϭ 7.4) and pressurized to 60 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…The vessels were isolated as previously described (Vamos et al 2013 ;Toth et al 2011 ). In brief, animals were anesthetized by intraperitoneal ketamin and decapitated immediately.…”
Section: Isolation and Preparation Of Carotid And Basilar Arteriesmentioning
confidence: 99%